Factors That Influence the Saving Behavior of Batam City Students - Johny Budiman; Yanty Yanty (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The concept of saving has been around for a long time, depending on each individual. In order to save, an individual must reduce his spending, save money for daily needs and even postpone consumption in the present for the future. The purpose of this study is to find out factors that influence the saving behavior of Batam city students. The total number of samples in this study amounted to 401 who were students of the city of Batam. This research was conducted by distributing questionnaires to obtain data which was addressed to Batam City Students. The distribution of this questionnaire was done by distributing the google form link through social media. Research result shows that: Financial literacy has a positive effect on intention and saving behavior. Saving motive has a positive effect on saving behavior. While, Intention, Parorental socialization and Self Control do not influence significantly on saving behavior financial literacy has no effect on saving behavior through intention as an intervening variable.